Design and experimental research of superconducting magnetic bearing for helium cold compressor. (March 2020) - Zou, Yincai; Shang, Jin; Guan, Xiang; Bian, Xing; Wu, Jihao; Li, Qing
Highlights: HTS magnetic bearing technology for helium cold compressor is analyzed. Design and measurement of HTS magnetic bearings is completed. A measurement platform was built, and differential measurement method are used. Designed HTS magnetic bearing has sufficient practical support performance. Abstract: In the large-scale superfluid helium cryogenic refrigeration system, the helium cold compressor faces the complex operating conditions of low temperature, high speed and sub-atmospheric pressure. The radial type high temperature superconducting (HTS) bearing of inner rotor and outer superconducting stator has the advantages and characteristics that they are suitable for being used in the helium cold compressor. Combining with the structure and operating parameters of a successful application of centrifugal active magnetic bearings in helium cold compressor, the design of radial HTS magnetic bearings considering bearing levitation performance and rotor dynamic performance was carried out. In order to ensure the accurate measurement of the rotor load and the rotor offset displacement, a performance measurement platform for the HTS magnetic bearing is built, and accurately weighed load rings and differential measurement method are used. The measured axial levitation force is 77 N when the offset displacement is 0.1 mm. And the axial stiffness is 771 N/mm and radial stiffness is about 385.5 N/mm in the measuring range. The first bending mode critical speed of the rotor system can reach 74, 108 rpm. The designed HTS magnetic bearing system can provide sufficient levitation force and support stiffness for the practical application of helium cold compressor system. The research work provides a guiding for the application of HTS magnetic bearings in helium cold compressor.